The Dawn of Liberation, 1945 - Churchill, Winston S. (War Speeches., 2013)
This fifth volume of wartime speeches and broadcasts from the Nobel Prize-winning prime minister brings the close of WWII to electrifying life. Legendary politician and military strategist Winston S. Churchill was a master not only of the battlefield, but of the page and the podium. Over the course of forty books and countless speeches, broadcasts, news items, and more, he addressed a country at war and at peace, thrilling with victory but uneasy with its shifting role on the world stage. In 1953, he was awarded the Nobel Prize for Literature for "his mastery of historical and biographical description as well as for brilliant oratory in defending exalted human values." During his lifetime, he enthralled readers and brought crowds roaring to their feet; in the years since his death, his skilled writing has inspired generations of eager history buffs. This fifth and final volume in the series of the great orator's wartime speeches, broadcasts, public messages, and other communications take readers through the momentous final events of World War II, culminating in Allied victory. Passionate, inspiring, informative, and amusing, no fan of WWII military history should be without this comprehensive, fascinating series.